An Evaluation of Accounting Problems for SMEs with GAP Analysis Method - Damayanti Damayanti; Destia Pentiana (Jurnal Ilmiah ESAI, 2015)
Most SMEs lack of understanding in preparing the financial statement as well as finance and accounting knowledge. Financial statements are necessary to find out information of financial position, financial performance, and cash flows of an entity that is useful to a large number of users in making economic decisions. It is assumed that the reluctance of SMEs is caused by the accounting cycle that is too burdensome and time-consuming and that it needs persons with special skills to manage it. This study was aimed at analyzing the gap between the quality of the design cycles and the expected design with the quality of simple accounting model expected by SMEs. The samples were obtained through purposive sampling method with 30 businessmen of SMEs (trade, Industry and services) that rarely prepare the financial statements. The data were collected through field survey with questionnaires and interviews. The data were analyzed using the GAP method. The results of this research note that all values in each dimension of GAP are negative, and the expectation value is greater than the perception value. The respondents were dissatisfied with the process / accounting cycle. This means that the design cycle used by regular public accounting is not done by the SMEs on the grounds that the cycle is too long, too complicated and time-consuming as well as the absence of the human resources with accounting expertise. Keywords: GAP Analysis, Cycle, Accounting Design, SMEs, Perceptions, Expectations.